Kadar Total Pigmen Klorofil dan Senyawa Antosianin Ekstrak Kastuba (Euphorbia pulcherrima) Berdasarkan Umur Daun - Maulid, Rendy Rohmatul (Prosiding KPSDA, 2015)
Studies on the content of the pigment chlorophyll and anthocyanin pigments in the leaves of plants kastuba at different levels of development has not been done. The leaves of this plant shows a very noticeable difference in color. At the level of developments in the oldest leaves (bottom) has a dark green color, while at the level of development of the youngest leaves (above) has a deep red color. This indicates that the difference in the color of the leaves with different levels of development shows the different types of pigments. The purpose of this study was to compare the content of the pigment chlorophyll and anthocyanin pigments in leaves kastuba (Euphorbia pulcherrima.) At different levels of development leaves.Â This research was conducted by the method of extraction and maceration using 70% ethanol. The extract obtained is used to test the color stability during storage for 2 days. After the leaves are extracted with 70% alcohol, chlorophyll content was measured using a spectrophotometer at Î» 649 and 665 nm and anthocyanin content was measured using a spectrophotometer at Î» 510 and 700 nm. The results showed that there are differences in chlorophyll and anthocyanin content in leaves of different levels of development. Between green leaves and red leaf, the highest levels of chlorophyll pigments in leaves of green, at the level of the first leaf (leaf oldest) and the lowest in the red leaves, at the level of the third leaf (leaves most young ). Levels of anthocyanin compounds in the leaves of different age levels turned out to show different results. Between green leaves and red leaf, the highest levels of anthocyanin compounds in the leaves that are colored green, at the lowest level (the oldest) and the lowest in the leaves red, at the top level (the youngest)